An Improved Second-Order Finite-Volume Algorithm for Detached-Eddy Simulation Based on Hybrid Grids (Communications in Computational Physics, 2018)
A hybrid grid based second-order finite volume algorithm has been developedfor Detached-Eddy Simulation (DES) of turbulent flows. To alleviate theeffect caused by the numerical dissipation of the commonly used second order upwindschemes in implementing DES with unstructured computational fluid dynamics(CFD) algorithms, an improved second-order hybrid scheme is established throughmodifying the dissipation term of the standard Roe's flux-difference splitting schemeand the numerical dissipation of the scheme can be self-adapted according to the DESflow field information. By Fourier analysis, the dissipative and dispersive features ofthe new scheme are discussed. To validate the numerical method, DES formulationsbased on the two most popular background turbulence models, namely, the one equationSpalart-Allmaras (SA) turbulence model and the two equation k−ω Shear StressTransport model (SST), have been calibrated and tested with three typical numericalexamples (decay of isotropic turbulence, NACA0021 airfoil at 60◦ incidence and 65◦ swept delta wing). Computational results indicate that the issue of numerical dissipationin implementing DES can be alleviated with the hybrid scheme, the resolutionfor turbulence structures is significantly improved and the corresponding solutionsmatch the experimental data better. The results demonstrate the potentiality of thepresent DES solver for complex geometries.